Granting of Property During Marriage as an Inherited Property in Indonesia - Nugroho, Eko Rial; Prabowo, Bagya Agung; Rohidin, Rohidin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study aims to discuss the granting of property by parents who are accepted at the time of marriage or are still bound by a valid marriage as inherited property. The problem is whether the property received at the time of marriage is innate property or joint property (gono gini). This research is normative research, with a legislative, conceptual and case approach, using primary legal materials, secondary legal materials, tertiary legal materials, research data collection using literature studies and document studies and analyzed qualitatively. The result of this research is that the property obtained from giving (grant) is innate property. Even though the grant is carried out when the husband and wife are still bound by a legal marriage or are still in the marriage period, the property is still innate or original property. The inherited property of each husband and wife, whether the property was obtained before marriage or during the marriage period obtained by each of them as a gift or inheritance as personal property. The position of inherited property belongs to and is under the control of each other, during the marriage as stipulated in Article 35 paragraph (2) of the Marriage Law and Article 86 of the Compilation of Islamic Law. The owner is free to take legal action against the property. The inheritance of the husband or wife and such property cannot be included in the scope of joint property unless the husband and wife have arranged it in the marriage agreement.